2017
DOI: 10.1515/phr-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidant–Antioxidant Equilibrium in the Blood of People with Sudden Sensorineural Hearing Loss After the First Hyperbaric Oxygen Therapy Session – A Preliminary Study

Abstract: The activity of selected antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) in erythrocytes, and the concentration of thiobarbituric acid reactive substances (TBARS) in blood plasma and erythrocytes, were determined in people subjected to hyperbaric oxygen (HBO) therapy due to sudden sensorineural hearing loss (SSNHL). Venous blood samples were taken immediately before entering the hyperbaric chamber and 5 min after leaving it. In the study group, two age subgroups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Because it is known that the imbalance of free radical formation or intensive consumption of antioxidant molecules leads to relatively decreased of biological macromolecules such as serum PON1 levels [9]. A balance shifting towards increased oxidative stress in SSNHL has been recently reported [2]. The most important finding of this study is, of course, the decrease in the PON1 concentrations in the serum of patients receiving HBOT.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Because it is known that the imbalance of free radical formation or intensive consumption of antioxidant molecules leads to relatively decreased of biological macromolecules such as serum PON1 levels [9]. A balance shifting towards increased oxidative stress in SSNHL has been recently reported [2]. The most important finding of this study is, of course, the decrease in the PON1 concentrations in the serum of patients receiving HBOT.…”
Section: Discussionmentioning
confidence: 54%
“…The use of HBOT has increased markedly in various diseases over the past decade [1]. The etiology for sudden sensorineural hearing loss (SSNHL) is defined in only 10 % of cases, whereas the rest are labeled as idiopathic [2][3][4]. So, how can be HBOT effective with a common molecular pathway in treatment of SSNHL?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paprocki et al [31], in a preliminary study in patients with SSNHL, demonstrated a reduction of the CAT activity approximately 5 minutes after the completion of a single HBO session. The largest reduction of the CAT activity was observed in patients under 35 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A pressure of approximately 0.25 MPa is used for the purposes of the treatment [10]. This pressure allows oxygenation of all organs and tissues of the body including the middle ear to resolve hearing loss symptoms besides breathing 100% oxygen with a special mask [11].…”
Section: Introductionmentioning
confidence: 99%